2014
DOI: 10.1890/130324
|View full text |Cite
|
Sign up to set email alerts
|

Biotic impacts of energy development from shale: research priorities and knowledge gaps

Abstract: Although shale drilling operations for oil and natural gas have increased greatly in the past decade, few studies directly quantify the impacts of shale development on plants and wildlife. We evaluate knowledge gaps related to shale development and prioritize research needs using a quantitative framework that includes spatial and temporal extent, mitigation difficulty, and current level of understanding. Identified threats to biota from shale development include: surface and groundwater contamination; diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…Petroleum extraction activity can be detrimental to bird populations through numerous mechanisms (Northrup and Wittemyer, 2013;Souther et al, 2014). Increased vehicle traffic can increase direct avian mortality near roads (Orłowski, 2008), and disturbance by heavy machinery can destroy nests (Van Wilgenburg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum extraction activity can be detrimental to bird populations through numerous mechanisms (Northrup and Wittemyer, 2013;Souther et al, 2014). Increased vehicle traffic can increase direct avian mortality near roads (Orłowski, 2008), and disturbance by heavy machinery can destroy nests (Van Wilgenburg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4 Thus, the appropriate management of biota in the landscape would ensure a sufficient buffer against environmental threats such as climate change and desertification. 4 In view of the above, the findings by Souther et al 2 should function as a stark wake-up call to all stakeholders of shale gas energy development in the Karoo; the locally targeted ecosystem needs to be considered in full to ensure cognisance of the realised impacts of fracking on the whole ecosystem. This biotic focus is especially relevant for the South African Karoo region because the method in question is directly threatening an already waterlimited environment.…”
Section: Develop Energy From Shale With Local Ecosystems In Mindmentioning
confidence: 99%
“…2 The authors concluded that energy development from shale gas often suffers from being ambiguous and incomprehensive across space: far too few peer-reviewed research papers particularly address the impact that fracking might have on the biotic elements in the landscape. This review therefore addresses the much-needed emphasis on including biodiversity conservation in assessing a fracking-targeted landscape.…”
mentioning
confidence: 99%
“…Research on this topic has proliferated exponentially over the last half decade; much research focuses on impacts associated with development (Sovacool 2014). Scientists have afforded particular attention to effects on the following: (1) water quality (Entrekin et al 2011, Jackson et al 2013, Olmstead et al 2013, Vidic et al 2013, Vengosh et al 2014, Llewellyn et al 2015, (2) air quality (Moore et al 2014), (3) global climate change (Alvarez et al 2012, Allen et al 2013, Newell and Raimi 2014, (4) biota/ecosystems (Drohan et al 2012, Kiviat 2013, Souther et al 2014, Milt et al 2015, (5) human health (New Brunswick Department of Health 2012, Kibble et al 2013, Adgate et al 2014, Kovats et al 2014 Institute for Applied Environmental Health 2014), (6) local and regional economics (Kinnaman 2011, Weber 2012, Fry et al 2015, and (7) community well-being (Jacquet 2014, Jacquet and Stedman 2014, Evensen 2015. These impacts could contribute to or challenge the prospects for sustainable and resilient futures in the communities where they are experienced.…”
Section: Introductionmentioning
confidence: 99%